2015
DOI: 10.5964/jspp.v3i1.117
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Conservatives Report Being Happier Than Liberals? The Contribution of Neuroticism

Abstract: Previous studies suggest that conservatives in the United States are happier than liberals. This difference has been attributed to factors including differences in socioeconomic status, group memberships, and system-justifying beliefs. We suggest that differences between liberals and conservatives in personality traits may provide an additional account for the "happiness gap". Specifically, we investigated the role of neuroticism (or conversely, emotional stability) in explaining the conservative-liberal happi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 39 publications
7
36
0
Order By: Relevance
“…As noted above, Napier and Jost () found that, in comparison with liberals, political conservatives report greater happiness and personal satisfaction and that this ‘happiness gap' is mediated, in part, by the justification of inequality. This pattern of results has been replicated many times over (Bixter, ; Burton, Plaks, & Peterson, ; Butz, Kieslich, & Bless, ; Choma, Busseri, & Sadava, ; Cichocka & Jost, ; Newman, Schwarz, Graham, & Stone, ; Okulicz‐Kozaryn et al ., ; Onraet, Van Assche, Roets, Haesevoets, & Van Hiel, ; Schlenker, Chambers, & Le, ; Wojcik et al ., ). These replications have not, however, prevented critics from disputing the basic notion that system justification serves a palliative function.…”
Section: Introductionmentioning
confidence: 65%
“…As noted above, Napier and Jost () found that, in comparison with liberals, political conservatives report greater happiness and personal satisfaction and that this ‘happiness gap' is mediated, in part, by the justification of inequality. This pattern of results has been replicated many times over (Bixter, ; Burton, Plaks, & Peterson, ; Butz, Kieslich, & Bless, ; Choma, Busseri, & Sadava, ; Cichocka & Jost, ; Newman, Schwarz, Graham, & Stone, ; Okulicz‐Kozaryn et al ., ; Onraet, Van Assche, Roets, Haesevoets, & Van Hiel, ; Schlenker, Chambers, & Le, ; Wojcik et al ., ). These replications have not, however, prevented critics from disputing the basic notion that system justification serves a palliative function.…”
Section: Introductionmentioning
confidence: 65%
“…More happiness among conservative people was larger in contexts with a conservative orientation, and lower or non‐significant in contexts with a liberal orientation. This difference favourable to conservatives has been attributed to factors such as high socioeconomic status, identification with a group with high collective esteem, emotional stability, and agreement with system justifying beliefs (Burton, Plaks, & Peterson, ). In addition, Napier and Jost (, study 1 and study 2) and Schlenker, Chambers, and Le (, study 1, study 2, and study 3) demonstrated an empirical link between conservatism and life satisfaction and happiness, which was mediated by system justification measures, after controlling for a range of socio‐demographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, another relevant contributor to the life satisfaction gap between conservatives and liberals is suggested byBurton, Plaks, and Peterson (2015): neuroticism. That is, conservatism is negatively correlated with neuroticism, the latter decreasing the reported life satisfaction.…”
mentioning
confidence: 99%